Assessment of mental health and quality of life status of undergraduate students in indonesia during covid-19 outbreak : A cross-sectional study - Karuniawati, Hidayah; Sari, Nila; Hossain, Md. Sanower; Wan Ismahanisa, Ismail; Haq, Aniq Hudiyah Bil; Yulianti, Tri; Taufik, Taufik; Sudarsono, Gardhika Rizky (MDPI, 2022)
The COVID-19 pandemic globally impacted physical, spiritual, and mental health (MH). The consequences significantly affected students’ quality of life (QoL) too. This cross-sectional study assessed MH status and its relationship to the QoL of college students in Indonesia. This study collected data (September 2021–April 2022) online using the depression, anxiety, and stress scale-21 (DASS-21) to measure MH and the world health organization quality-of-life scale (WHOQoL-BREF) to measure the QoL. The data were analysed using SPSS with a bivariate and multivariate linear regression test. A total of 606 respondents participated in this study, with the majority being women (81.0%), aged 21–27 years (44.3%), and unmarried (98.5%) respondents. We observed 24.4% (n = 148) moderate depression, 18.3% (n = 111) very severe anxiety, and 21.1% (n = 128) moderate stress status. The QoL measurement determined that a moderate QoL in the physical and environmental health domains (>70%) and poor QoL in the psychological health domain (58.3%) were found. Gender, age, family support, history of COVID-19 diagnosis, family with COVID-19 diagnosis, vaccination status, and physical symptoms are significantly associated with MH status and QoL (p-value < 0.05). This study demonstrated that COVID-19 was negatively related to college students’ MH and QoL. Targeted interventions may be needed to ameliorate both MH and QoL.